PENINGKATAN USAHA OPAK PEDAS MANIS PAK SULAWI CAP ANGSA DI KAVLING LAMA SWADAYA BATUAJI KOTA BATAM - Suswanto Ismadi Megah; Sri Sugiharti; Rasyid Ridho Harahap; Calvin Avalycotesvara Arintiarno Lee (PUAN INDONESIA, 2026)
Small and medium enterprises managed by Mr. Sulawi are something extraordinary, because with a very minimal educational background but are able to provide jobs for many people. In this PKM activity, input is provided on how this UMKM business can grow rapidly. Home-based bread businesses that are managed by bringing the Brand Image from their hometown, namely Sweet Spicy Opak Business of Pak Sulawi’s Angsa Brand, are able to compete in big cities like Batam. With the name Sweet Spicy Opak Business of Pak Sulawi’s Angsa Brand ". However, the obstacles experienced by the bread entrepreneur, Mr. Parno, for example, business capital to develop bread, by looking for credit cannot be done, but the presence of Community Service activities (PKM) from the University of Riau Islands provides input by making bread design banners, advertisements, and by sponsoring films made by academics from the University of Riau Islands (UNRIKA), in addition, halal permits and certification have also been made. The purpose of the community service activities carried out during the PKM period is to help the bread company " Sweet Spicy Opak Business of Pak Sulawi’s Angsa Brand " in expanding its marketing area by creating new marketing methods through social media and helping other marketing activities such as providing banners and involving local youth to participate in increasing sustainable economic activities. Thus, the Sweet Spicy Opak Business of Pak Sulawi’s Angsa Brand business can grow and help the economy of local residents by absorbing labor, thereby improving the economy of residents around the Kavling Lama, Batuaji District, Batam City.. Keywords— Improving, Opak Pedan dan manis, Micro, Small and Medium Enterprises